Lower limb muscle activation patterns and physiological responses obtained using binding pedals during bicycle exercise: the differences in the cycling cadence, cycling time and experience of the subjects - Satake, T.; Kume, M.; Yoshida, T.; Maki, M.; Tsuneoka, H. (Advances in Exercise and Sports Physiology, 2015)
This study aimed to clarify lower limb muscle activation patterns and physiological responses obtained using clipless pedals (so-called "Binding pedals," BP) during bicycle exercise. In experiment 1, six trained cyclists (TC) and seven novice cyclists (NC) performed a bicycle pedaling task for five minutes using either BP or normal pedals (NP) under four experimental conditions: cadence = 50 and 100 rpm, output power = 100 and 150 W. In experiment 2, five TC performed a bicycle pedaling task for 60 minutes using BP or NP at 100 rpm with an output power of 150 W. The relative electromyogram (EMG) activity of the tibialis anterior (TA) and gastrocnemius caput laterale (GL) muscles was significantly lower in the BP group than in the NP group, and this phenomenon was more noticeable when pedaling at 50 rpm among the TC, but not NC. The relative EMG activity of the TA muscle was significantly greater in the NP than in the BP group at the end of the 60-minute exercise period. The rate of perceived exertion was significantly lower and the heart rate tended to be lower in the experiments performed with BP than in those performed with NP during 60 minutes of cycling exercise. These results suggest that the effects of the use of binding pedals on the leg muscle activity pattern and physiological responses depend on differences in the individual`s experience with BP, cycling cadence and cycling time during bicycle exercise.